URGENSI DIMENSI ETIS PESAN AL-QUR’AN DALAM PENGEMBANGAN HUKUM ISLAM (Mazahib, 2015)
This article tries to reveal the ethical dimension of the urgency message of the Qur'an in the development of Islamic law, especially in relation to dealing with global issues today. Islamic Jurisprudence (Fiqh), as a discipline of Islamic law must be able to answer the problems of humanity in a "good and proper" manner in order to be relevant. In this regards, understanding of the theory of Islamic law (Usul al-Fiqh), as the methodology of understanding Islamic teachings, must be willing to open up and do not be bound by the classical theory which is exclusive-deductive in nature. It needs to and collaborate with other scientific disciplines, such as sociology, anthropology and so forth. One alternative way is by paying attention to the ethical messages of the Qur'an which are more normative-universal. To find out which messages are normative and the particular historical-technical nature, the method of "double movement" offered by Fazlur Rahman deserves a careful attention.